Socio-economic challenges of unaccompanied minors seeking to cross Zimbabwe-South Africa border - Mabvurira, Vincent; Matlakala, Frans Koketso; Masilo, Daniel Tuelo (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study sought to explore the socio-economic challenges of unaccompanied child migrants in Zimbabwe’s Beitbridge district. The study examined factors that force children to illegally cross/ seek to cross the Zimbabwe- South Africa border without guidance and it also examined challenges faced by the child migrants during their transit. Micheal Ungar’s resilience across cultures theory informed the study. The study adopted a qualitative research approach where in-depth interviews, focus group discussion and key informant interviews were triangulated to collect data. The data were analysed using thematic content analysis. Findings revealed that children leave their homes due to poverty, abuse and neglect among other reasons. These determinants were identified as the major factors that push children away from home in search of better opportunities in other countries. The study also revealed that on their way to South Africa children face abuse from transporters and there is spread of diseases due to sexual abuse. The study recommends that the government of Zimbabwe as the leading agent for the welfare of children should devise measures that strengthen families so that they contain children even in cases of life shocks. The study also recommends for closer collaboration between the government and private partners in improving the economic base of families. Social workers and other helping professions were also recommended to train parents on some good parenting strategies that help to improve the welfare of their children.